The Woman Question in the novels by the Bronte Sisters - Anis, Rehnuma Bint (IIUC Studies, 2009)
The Victorian period lasted more than half a century. During this time England changed radically in almost all respects. One of these was the rising consciousness of women about their rights and potentials. Soon, the social awareness was transmitted to literature. In retrospect we find that many women writers emerged at this critical juncture in history when women were pleading to be given voice, to achieve their rights and to be given an opportunity to come out of the shells of quiet submission enforced upon them and achieve something of their own. Three sisters living deep in the Yorkshire moors surprised the world by taking part in this ongoing struggle. This article attempts to evaluate their contributions towards achieving women's rights in English history. doi: 10.3329/iiucs.v3i0.2629 IIUC STUDIES Vol. - 3, December 2006 (p 19-30)